Propuesta de diseño de proceso para la formación de una geored a partir de fibra natural de bambú (guadua angustifolia) como refuerzo de un geotextil para la empresa Pavco-Wavin Colombia (2021)
With this project, it is sought to develop a process design to obtain a Geocomposite material, industrially called Geodrén, for the company PAVCO-Wavin; implementing a more environmentally friendly material that in turn provides greater and better characteristics to the final product, which is why the raw material on which the project is based is bamboo fiber from the Guadua Angustifolia species. Taking into account the information available on bamboo fiber, an alternative process to the one that the company has been working is proposed, with the aim of replacing the synthetic Geogrid acquired from an external supplier. The mechanical properties that characterize this compound is its resistance to tension, compression and modulus of elasticity, it must also present chemical resistance to external agents, which is why it must be based on the characterization of the fiber in order to supply these requirements, since these are the ones who determine its mechanical properties at the same time, it is necessary to develop a process design where it is possible to obtain a finished product as a drainage system, finally, the financial analysis is developed, evaluating indicators such as : IRR, TIO, NPV, Profitability Index and Cost / Benefit Ratio to identify the viability of the project.